The Use of Regression Models with Supply Chain Management to Increase Financial Satisfaction of Generation Z - Hafni, Layla; Renaldo, Nicholas; Chandra, Teddy; Thaief, Ilham (ExcelingTech, 2020)
Abstract- The low level of financial satisfaction of Generation Z will make them stressed about their future. This study aims to improve the financial satisfaction of Generation Z with Multiple Linear Regression and Regression Models with interaction supply chain strategies. Samples were used as many as 246 respondents from 263 questionnaires distributed in Pekanbaru City using convenience and purposive sampling methods, namely the Generation Z age criteria. The results showed that in the first model there was a significant influence of Financial Behavior and Financial Knowledge partially on Financial Satisfaction. While the insignificant influence is partially affected by Financial Attitude and Financial Literacy on Financial Satisfaction. While the second research model shows that there is a significant influence on Financial Knowledge and Financial Literacy partially on Financial Satisfaction, while the insignificant influence is on the influence of Financial Attitude and Financial Behavior partially on Financial Satisfaction. The second model also uses supply chain strategies where Financial Knowledge is used as a moderator. The results show there is a significant influence of Financial Literacy on Financial Satisfaction but there is no significant effect of Financial Attitude and Financial Behavior partially on Financial Satisfaction. The first research model provides a better explanation than the second model. Both models show the significant influence of Financial Knowledge. Increasing Financial Knowledge and Financial Literacy through education will be very beneficial for Generation Z for their Financial Satisfaction.